Effect of Steric Hindrance of Butylammonium Iodide as Interface Modification Materials on the Performance of Perovskite Solar Cells. Issue 7 (18th March 2022) - Zhao, Xusheng; Dong, Jun; Wu, Daofu; Lai, Junan; Xu, Cun Yun; Yao, Yanqing; Yang, Xiude; Tang, Xiaosheng; Song, Qunliang
Abstract : The efficiency and stability of perovskite solar cells (PSCs) can be effectively improved by interfacial modification with butylammonium iodide (BAI). However, the steric hindrance of BAI is not explored. Herein, BAI with different steric hindrances, that is, n‐ BAI, iso‐BAI ( i‐ BAI), and tert‐BAI ( t‐ BAI), are systematically studied as interface modification materials between (FAPbI3 )0.95 (MAPbBr3 )0.05 and spiro‐OMeTAD in PSCs. It is found that the efficiency and humidity stability of devices gradually increase in the order of t‐ BAI‐, i‐ BAI‐, n‐ BAI‐modified ones. This seems that the larger steric hindrance hinders BAI diffusion to the grain boundary, resulting in the reduction of grain boundary passivation and the residue of excessive BAI on the surface of perovskite films. Excessive BAI is equivalent to new defects and can block hole transport. As the steric hindrance increases from n‐ BAI to i‐ BAI, and further to t‐ BAI, the device with n‐ BAI modification shows the highest power conversion efficiency (PCE) of 20.67% with excellent stability in air with a humidity of 20–30%, keeping 80% of the original PCE after 60 days. It is believed that this study can guide the structural selection of modified materials at the interface between perovskite and hole transport layer with n–i–p structure. Abstract : The increase in butylammonium iodide (BAI) steric hindrance weakens its diffusion to grain boundary, resulting in excessive BAI residue on the surface of perovskite films. Because diffusion to grain boundary affects the passivation of grain boundaries and excessive BAI on the surface blocks hole transport, the photovoltaic performance of the device decreases gradually with the increase in BAI steric hindrance.